A ação da igreja no cuidado pastoral com pessoas com HIV - Hoppe, Walter (2013)
This study aimed to reflect the care in the pastoral practice developed with the people who live with HIV/Aids and enrich it with texts that reflect on this practice. In this study an interdisciplinary approach was used. The study also reflects about the church, considering that the people, who live with HIV/Aids, are parts its body. In this perspective the question about the person s position as well as the position of the Church in combating the epidemic was raised. By revising the literature, a critical reading has been done, looking for ways to help the caregiver in his/her pastoral practice. Taking care of life, taking care of himself, taking care of another and be cared by God that s how this first moment envy. The description of the pastoral practice developed at the public hospital Hospital Centenário in São Leopoldo, RS, is introduced with the training of visitors and the organization of the spiritual visitation in the hospital. Lastly, this study intent to show the challenges that the illness (sickness) brings to the Church as a faith community, Christians individual persons and society. There is a need for the Church to reflect about herself, her theology; the ways the Word was conceded, how to care, listen, forgive, touch, and allow life and to be faithful to her call today, allowing the cure of life.